Non-differentiable functionals and singular sets of minima - Kristensen, J; Mingione, G (2005)
We provide bounds for the Hausdorff dimension of the singular set of minima of functionals of the type ∫Ω F(x, v, Dv), where F is only Hölder continuous with respect to the variables (x, v). © 2004 Académie des Sciences. Published by Elsevier SAS. All rights reserved.